Platinum-group metal half-sandwich complexes of 1-(α-d-glucopyranosyl)-4-hetaryl-1,2,3-triazoles: synthesis, solution equilibrium studies, and investigation of their anticancer and antimicrobial activities - Zaki, Alshimaa I.; Sipos, Adrienn; Kacsir, István; Kovács, Nóra Ildikó; Kerekes, Éva; Szoták, Evelin; Freytag, Csongor; Demény, Máté; Révész, István; Buglyó, Péter; Bényei, Attila; Janka, Eszter Anna; et al. (Frontiers in Chemistry, 2025)
Although platinum-based complexes are pivotal in chemotherapy, their clinical use is limited by toxicity and resistance. Previously, we identified a set of osmium, ruthenium, and iridium half-sandwich complexes of 1-N-(β-d-glucopyranosyl)-4-hetaryl-1,2,3-triazole-type N,N-chelators with potent and selective activity against a large set of diverse neoplasia cell models and multiresistant Gram-positive bacteria (methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-resistant Enterococcus (VRE)). Our aim in this study was to assess how the configuration of the C1 carbon in the glucose moiety affects the biological activity of the complexes. Thus, 1-N-(α-d-glucopyranosyl)-4-hetaryl-1,2,3-triazoles were synthesized and used as N,N-bidentate ligands to result in half-sandwich type complexes analogous to the earlier reported ones. Overall, the newly prepared complexes with the α-anomeric carbohydrate moiety had similar biological properties to the complexes with the β-anomeric carbohydrate unit in terms of their biological activity on cancer cells or primary human cells. Importantly, the bacteriostatic property of the complexes with an α-anomeric sugar moiety was inferior to that of the complexes containing the β-anomer.